LEGALITY OF CONTRACT IN ISLAMIC LAW PERSPECTIVE - Fatkhul Wahab (Fakultas Syariah - IAI Al-Qolam Malang, 2021)
In the concept of Islamic economics, the position of the contract is very urgent in determining the legality of a transaction, both in the view of humans as the perpetrators of the contract and in the view of Islamic law which regulates human interactions and transactions in all its forms. The contract in this transaction can be in the form of a tabarru contract which aims to help each other among humans or a profit-oriented tijarah contract. Islamic law strongly emphasizes this legality so that there is no disappointment for either of the two parties who make transactions due to defects in Islamic law, either intentionally or unintentionally. The legality of the contract in this transaction must meet the elements consisting of the subject of the contract, the object of the contract, and the sighat of the contract with each of the conditions set by Islamic law.